URGENSI PENERAPAN KONSEP GODLY CONSTITUTION (KONSTITUSI DENGAN NILAI KETUHANAN) DALAM PENGUJIAN PERKARA KONSTITUSIONAL DI MAHKAMAH KONSTITUSI - As’ari Taufiqurrohman; Suryani Suryani; Dwi Edi Wibowo (LPPM Universitas Pekalongan, 2022)
The study of the constitution could not be covered by the scope of rechstate only, but also compare it with pancasila. To strengthen godly values in the concept of the constitution, we should understand the constitutional concept which follows the rule of law with basic type of the country and nationality (such as culture, religion or norms). To compare it, we have to discuss a more significant idea about the state. This research promoted to explain about the extent of religious content as well as prime religion which recognized on the constitution in order to Judicial review process in Indonesian Constitutional Court, by using normative legal research. Finally, this research describes how important the religion concept (in each manuscript) to the body of the constitution, to reach “the living constitution” and to show the other side of the godly values with various theories of laws especially from the Indonesian constitutional court as the guardian of ideology.